Bis(acyl)phosphide ‐ Ambidentate Ligands for the Synthesis of Group 14 and 15 Main Group Element Compounds. Issue 3 (1st March 2023) - Widera, Anna; Conti, Riccardo; Schrader, Erik; Aebli, Marcel; Wörle, Michael; Grützmacher, Hansjörg
Abstract: The reactivity of the bis(acyl)phosphide ion [P(COR)2 ] − (BAP −, R=Ph, Mes) with silicon halides SiX4 (X=Cl, Br) and pnictogen chlorides ECl3 (E=As, Sb and Bi) was investigated. The reaction with SiX4 leads to the hexacoordinate silanes SiX2 (BAP)2 in which BAP − is coordinated in the chelating κ 2 ‐O, O′ mode, analogously to acac − . Unexpectedly, the coordination behaviour of BAP − differs from the one of acac − in the interpnictogen compounds E(BAP)3 (E=As, Sb) in which the formation of E−P bonds is favoured over κ 2 ‐O, O′ chelation via the oxygen centres. Finally, the reaction of BiCl3 with three equivalents of Na(BAP) leads to the formation of red, crystalline Bi2 (BAP)4, an air stable dibismuthine, as product of a redox reaction. Abstract : The coordination behaviour of the bis(acyl)phosphide ion (BAP − ) with group 14 and 15 elements was investigated. Differently than its lighter analogue, acetylacetonate (acac − ), BAP − coordinates either in a chelating manner via the oxygen atoms or via the phosphorus atom thus leading to the formation of the interpnictogen bonds P−As, P−Sb and P−Bi.